YCbCr 컬러공간에서 구성성분간의 상관관계를 이용한 축소된 채도 정보의 다중 모드 재구성 - 김영주(Young-Ju Kim) (한국콘텐츠학회 논문지, 8(2), 2008)
This paper investigates chrominance reconstruction methods that reconstruct subsampled chrominance information efficiently using the correlation between luminance and chrominance components in the decompression process of compressed images, and analyzes drawbacks involved in the adaptive-weighted 2-dimensional linear interpolation among the methods, which shows higher efficiency in the view of computational complexity than other methods. To improve the drawback that the spatial frequency distribution is not considered for the decompressed image and to support the application on a low-performance system in behalf of 2-dimensional linear interpolation, this paper proposes the multi-mode reconstruction method which uses three reconstruction methods having different computational complexity from each other according to the degree of edge response of luminance component. The performance evaluation on a development platform for embedded systems showed that the proposed reconstruction method supports the similar level of image quality for decompressed images while reducing the overall computation time for chrominance reconstruction in comparison with the 2-dimensional linear interpolation. 본 논문은 압축된 영상의 복원 과정에서 축소된 채도 정보를 휘도와 채도 성분의 상관관계를 이용하여 효율적으로 재구성하는 기법들에 대해 살펴보고, 기존에 계산 복잡도 측면에서 효율성을 보인 적응적 가중치를 가진 2차원 선형 보간법에 대해 문제점을 분석하였다. 그리고 본 논문은 2차원 선형 보간법에 대해 영상의 공간 주파수 분포를 고려하지 않는 문제점을 개선하고 저성능 시스템에 적용하기 위해 휘도 성분의 에지 반응도에 따라 계산 복잡도가 서로 다른 재구성 기법을 적용하는 다중 모드 재구성 기법을 제안하였으며, 임베디드 시스템 개발 플랫폼에서의 성능 평가 실험을 통해 유사한 수준의 복원 영상의 품질을 지원하면서 채도 재구성을 위한 계산 시간을 상대적으로 줄이고 있음을 확인하였다.